Circadian blood pressure profile in patients with chronic obstructive pulmonary disease and arterial hypertension on baseline therapy - Konopkina, L.I.; Dziublyk , Ya.O.; Babets , A.A.; Shchudro, O.O. (Medicni Perspektivi, 2025)
The aim of the study was to analyse the effect of a long-acting muscarinic antagonist and an inhaled corticosteroid on the circadian profile, blood pressure (BP) variability, and circadian rhythm disturbances in patients with chronic obstructive pulmonary disease (COPD) and concomitant arterial hypertension, based on ambulatory blood pressure monitoring (ABPM) data during long-term use of these therapies. A total of 86 patients with COPD of GOLD stage II and III (Global Initiative for Chronic Obstructive Lung Disease) and stage II hypertension (men – 67 (77.9%), women – 19 (22.1%), mean age – 62 (56; 74) years) in a stable phase of the disease were examined. All patients received continuous combined antihypertensive therapy, which remained unchanged for at least 6 months. Depending on the degree of bronchial obstruction and the type of inhalation therapy, patients were divided into three subgroups: subgroup 1 included 34 patients with GOLD stage II airflow limitation who received only a bronchodilator (tiotropium bromide 18 μg per day); subgroup 2 included 23 patients with GOLD stage III airflow limitation who received both a bronchodilator (tiotropium bromide 18 μg/day) and an inhaled corticosteroid (ICS) (beclometasone dipropionate 250 μg twice daily); subgroup 3 included 29 patients with GOLD stage III airflow limitation who received only a bronchodilator (tiotropium bromide 18 μg/day), despite indications for combined therapy. All patients achieved target office blood pressure levels (<140/90 mmHg); however, ABPM revealed elevated mean daily blood pressure (>130/80 mmHg) in 60 out of 86 patients (69.8%), predominantly in subgroup 2 (p<0.05). At night, mean diastolic blood pressure in subgroup 2 was 67 (57; 79) mmHg, higher than in subgroup 1 (60 (51; 69) mmHg; p<0.05). Blood pressure variability also increased with severe bronchial obstruction: in subgroup 3, night-time systolic BP variability reached 14 (13; 17) mmHg (p<0.05 vs. other groups). A normal circadian profile (“dipper”) was observed in 25 patients (41.7%), whereas pathological types were recorded in 35 patients (58.3%) – “non-dipper” and “night-peaker” in 33 cases (94.3%) and “over-dipper” in 2 cases (5.7%). Disturbances in nocturnal blood pressure reduction were most frequent in subgroup 2 (p<0.05). Thus, patients with COPD and clinically stable (medically compensated) concomitant hypertension generally exhibit normal office blood pressure values. However, nearly 70% of such patients show elevated night-time blood pressure according to ABPM. Patients receiving ICS for COPD therapy predominantly demonstrate pathological circadian BP patterns (“non-dipper” and “night-peaker”), whereas a normal circadian BP pattern (“dipper”) is more frequent in patients treated with a long-acting muscarinic antagonist as baseline COPD therapy (p<0.05). In patients with COPD and concomitant hypertension, blood pressure should be monitored not only by office measurements but also using ABPM; in cases of ABPM abnormalities, patients require dynamic follow-up by a cardiologist.